2011
DOI: 10.2752/175303711x12998632257620
|View full text |Cite
|
Sign up to set email alerts
|

The Public Face of Zoos: Images of Entertainment, Education and Conservation

Abstract: Abstract:The contemporary justification for zoos is based on their ability to act as sites of wildlife conservation. Alongside this is the reality that zoos have historically been defined as sites for the entertainment of the general public and continue to be dependent on the revenue raised through visitor receipts. Consequently, zoos are, today, identified as sites of conservation, research, education, and entertainment. In recognition of this the aim of this paper is to assess the image that zoos are current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 25 publications
2
71
0
2
Order By: Relevance
“…They found that zoos and aquariums can enhance visitors' knowledge and understandings of wildlife and conservation, as well as their con-nection to nature, prompting individuals to reconsider their role in environmental problems and conservation actions. That is in line with the goal of the modern naturalistic zoo exhibits to improve animal welfare standards through environmental enrichment and naturalistic features in order to reduce their behavioural and physiological problems, like stereotypic behaviours or obesity and nutrient deficiencies (Anderson et al, 2008;Carr and Cohen, 2011;Marino et al, 2010).…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…They found that zoos and aquariums can enhance visitors' knowledge and understandings of wildlife and conservation, as well as their con-nection to nature, prompting individuals to reconsider their role in environmental problems and conservation actions. That is in line with the goal of the modern naturalistic zoo exhibits to improve animal welfare standards through environmental enrichment and naturalistic features in order to reduce their behavioural and physiological problems, like stereotypic behaviours or obesity and nutrient deficiencies (Anderson et al, 2008;Carr and Cohen, 2011;Marino et al, 2010).…”
Section: Introductionsupporting
confidence: 70%
“…In this respect, the Zagreb Zoo visitors are similar to botanic gardens visitors (Ballantyne et al, 2008;Connell, 2004) and other modern-day zoo and aquarium visitors (Jordaan and du Plessis, 2011; Ryan and Saward, 2010), determining zoos as primarily places of family-oriented trips, and emphasizing enjoyment in animals, nature, and spending quality time with children, friends and family, rather than learning. Even though education is not very high on the list of motivators for visiting the Zagreb Zoo, modern zoos should be places where visitors learn about animals and should demonstrate how an individual can contribute to the survival of endangered species (Carr and Cohen, 2011;Lee, 2015). If the Zagreb Zoo is to introduce more educational activities, they need to give careful consideration to how these are planned and promoted.…”
Section: S O C I O L O G I J a I P R O S T O Rmentioning
confidence: 99%
See 3 more Smart Citations